Electrospun Nanofiber Electrodes with in situ Exsolved Nanocatalysts for Symmetrical SOCs - Lach, Jakub; Zheng, Kun; Gogacz, Michał; Czaja, Paweł; Luo, Jie; Brzoza-Kos, Agnieszka (My University, 2023)
In this work, A-site deficient $Sm_{0.9}Ba_{0.9}Mn_{1.8−x}Fe_{x}Co_{0.1}Ni_{0.1}O_{6−δ}$ (x = 0, 0.45 and 0.9) double perovskites with in situ exsolved nanoparticles were successfully obtained and evaluated as electrode materials for symmetrical Solid Oxide Cells (SOCs). All obtained oxides belong to the P4/nmm tetragonal system, and a phase transition from P4/nmm to P4/mmm was recorded by the HT-XRD in the air. The in situ exsolution of nanoparticles has been confirmed by the XRD and SEM analysis. The proposed materials present excellent redox stability and moderate thermal expansion coefficients. Electrospun nanofibers (with 150 nm diameter) were successfully fabricated, indicating an excellent potential application in the electrode. The results show the developed A-site deficient double perovskites with iron doping at Mn-site can be potentially applied as novel electrode materials for symmetrical SOCs.
Keywords: In situ exsolution; A-site deficiency; Double perovskites; Nanocatalysts; Symmetrical solid oxide cells